A Report on the Crystal Structure of Monoprotonated Tripodal Ligand Tris(2,2’-bipyrid-6-yl) Methanol: Potential Precursor for COF - CuhaWijay Sathiyajith; James C. Knight; Benson Kariuki; Peter G. Edwards (Chemistry and Biochemistry: Research Progress Vol. 3, 2025)
Versatile drug delivery systems could be based on porous materials which could encapsulate active pharmaceutical ingredients. These composite materials could be based on organic-inorganic, organic-organic hybrid systems and called metal-organic frameworks (MOFs) and covalent organic frameworks (COFs) respectively. The tripodal bipyridine-based ligand tris(2,2’-bipyrid-6-yl) methanol (L1) was shown in our previous work to have a strong steric preference for trigonal prismatic coordination environments with a series of transition metals. Herein we report the crystal structure of the ligand framework, isolated in its monoprotonated form with a perchlorate counterion. The structure was solved in a monoclinic space group C2/c with cell parameters, a = 21.5885(3), b = 11.7485(3), c = 24.6939(6) Å, \(α\) = 90°, \(β\) =110.790(1) °, \(γ\) = 90°, volume = 5855.4(2) Å3, Z = 8. The 1H NMR of the protonated ligand is similar to the parent ligand and showed the compound retained its 3-fold symmetry and all bipyridine groups were equivalent. This study has shown that the solid state structure of the protonated form of the ligand (Tbpym-L1) has a structure consisting of the three bipyridyl moieties connected to a central carbon. The pyridyl rings connected directly to the central carbon all have their nitrogen donor pointing to the centre of the molecule, perhaps suggesting they all interact with the proton. The potential application of the protonated tripodal ligand in coordinate covalent organic frameworks (COFs) and metal-organic polyhedral (MOP) based drug delivery systems (DDS) is also proposed. Additionally, rhenium or ruthenium-coordinated radiotherapeutic agents are also envisaged.